Gene expression profile induced by oral administration of baicalin and gardenin after focal brain ischemia in rats - ZHANG Zhan-jun; WANG Zhong; ZHANG Xiao-yan; YING Kang; LIU Jian-xun; WANG Yong-yan (Acta Pharmacologica Sinica; Vol 26, No 3 (March 2005): Acta Pharmacologica Sinica, 2016)
Aim: To investigate differential gene expression and the pharmacological mechanism of baicalin and gardenin in focal cerebral ischemia in rats with high-density cDNA microarray. Methods: Rat left middle cerebral arteries were occluded and treated with either baicalin or gardenin. The pharmacological effects were investigated using the difference in infarction areas before and after treatment, which were determined by 2,3,5-triphenyltetrazolium chloride (TTC) staining. Gene expression was demonstrated using a “Biostar40S” gene microarray. Semiquantitative reverse transcription-polymerase chain reaction (RT-PCR) was used to verify the result of the selected genes. Results: Both baicalin and gardenin reduced the infarction areas in focal cerebral ischemia rats (P